DEVELOPMENT AND CHARACTERIZATION OF A CATALYTIC MEMBRANE FOR VOLATILE ORGANIC COMPOUND COMBUSTION (Nigerian Journal of Technology, 2018)
Platinum-alumina (Pt/?-Al2O3)catalytic membranes were obtained using the reservoir technique for the combustion of volatile organic compounds (VOCs). The membranes were characterized by scanning electron microscopy and energy dispersive X-ray analysis (SEM-EDXA) observation, Brunauer-Emmett-Teller (BET) measurement and gas permeation. Propane (C3H8) and n-butane (C4H10) combustion was obtained. Maximum VOC conversion for propane and n-butane of 93 and 48 (%) was achieved on 3.52wt% Pt catalyst at a temperature of 427 and 259 (0C) and flow rates of between 185-222 and 295-379 (ml/min) without any changes in conversion. The combustion results of C3H8 and C4H10 corroborate with literature on Pt/?-Al2O3 catalysts. The conversion was achieved using flow-through catalytic membrane reactor operating in the Knudsen flow regime. http://dx.doi.org/10.4314/njt.v37i4.18